Case studies in assisted reproduction : common and uncommon presentations - Macklon, Nick S.; Fatemi, Human M.; Norman, Robert J.; Patrizio, Pasquale (Cambridge : Cambridge University Press, 2015)
Clinical case studies have long been recognized as a useful adjunct to problem-based learning and continuing professional development. They emphasize the need for clinical reasoning, integrative thinking, problem-solving, communication, teamwork and self-directed learning - all desirable generic skills for health care professionals. This volume contains a selection of cases on assisted reproduction that will inform and challenge reproductive medicine practitioners at all stages in their careers. Both common and uncommon cases are included. The aim is to reinforce diagnostic skill through careful analysis of individual presenting patterns, and to guide treatment decisions. Each case consists of a clinical history, examination findings and special investigations, before a diagnosis is made. Clinical issues raised by each case are discussed and major teaching points emphasized. Selective references are provided. The book provides a useful complementary adjunct to existing textbooks of reproductive medicine, and an excellent resource for teaching and continuing professional development.
Title from publisher's bibliographic system (viewed on 13 May 2016).